2011
DOI: 10.1007/s00709-010-0257-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential antioxidative responses to dehydration-induced oxidative stress in core set of foxtail millet cultivars [Setaria italica (L.)]

Abstract: Foxtail millet (Setaria italica L.) known as a relatively drought-tolerant crop across the world is grown in arid and semi-arid regions. To the best of our knowledge, no systematic study on drought tolerance screening of foxtail millet germplasm being a drought-tolerant crop has been reported so far. To explore genetic diversity of drought-induced oxidative stress tolerance in foxtail millet, we employed lipid peroxidation measure to assess membrane integrity under stress as biochemical marker to screen 107 cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 41 publications
4
71
0
Order By: Relevance
“…In the present study, the MDA content significantly increased from (T 1 -control to T 3 -8% PEG) but the increment in susceptible genotypes is higher than the tolerant genotypes. These results are consistent with the findings of Lata et al, (2010) who reported that the dehydration tolerant genotypes showed considerably lower levels of lipid peroxidation (MDA) as compared with dehydration sensitive genotypes, indicating its better cell membrane integrity in tolerant genotypes. Similar observation are made by the Moussa et al, 2008 andChugh et al, 2011 who suggested that the MDA content in sensitive genotypes both under non stress and water stress condition was higher as compared to the tolerant genotypes.…”
Section: Lipid Peroxidation (Mda)supporting
confidence: 92%
“…In the present study, the MDA content significantly increased from (T 1 -control to T 3 -8% PEG) but the increment in susceptible genotypes is higher than the tolerant genotypes. These results are consistent with the findings of Lata et al, (2010) who reported that the dehydration tolerant genotypes showed considerably lower levels of lipid peroxidation (MDA) as compared with dehydration sensitive genotypes, indicating its better cell membrane integrity in tolerant genotypes. Similar observation are made by the Moussa et al, 2008 andChugh et al, 2011 who suggested that the MDA content in sensitive genotypes both under non stress and water stress condition was higher as compared to the tolerant genotypes.…”
Section: Lipid Peroxidation (Mda)supporting
confidence: 92%
“…According to SCANDALIOS (2005), damage in the plasma membrane is often associated with leakage of electrolytes and cell death; and therefore, peroxidation has been used as a marker in the selection of cultivars (SHAO et al, 2005;LATA et al, 2011). The variety RB867515 showed no significant difference of MDA in leaf tissues exposed to combined stresses (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Water-stressed wheat, rice, and foxtail millet plants had lower RWC as compared to the control plants (Siddique et al 2001 ;Lata et al 2011a ). Siddique et al ( 2001 ) reported a decline in LWP, RWC, and Tr with a simultaneous increase in leaf temperature in drought-stressed wheat and rice plants.…”
Section: Water and Nutrient Uptakementioning
confidence: 96%